2011
DOI: 10.1203/pdr.0b013e31820bc13a
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin Is Present in High Quantity in Human Milk and Has a Vasorelaxing Effect on Newborn Rat Mesenteric Arteries

Abstract: Breast milk reduces the incidence of necrotizing enterocolitis (NEC). BH4 is a cofactor for endothelial NOS (eNOS). Reduced BH4 levels, or its oxidation to dihydrobiopterin (BH2), uncouple eNOS resulting in formation of reactive oxygen species (ROS) that have been implicated in the pathogenesis of NEC. We evaluated colostrum and mature breast milk, as well as infant formula, BH4 and BH2 content. In addition, we tested the BH4 effect on the newborn rat mesenteric arterial vascular tone. BH4 and BH2 content incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Breast milk, as opposed to infant formulas, has a high BH4 content (46), and IHPS rarely occurs in infants that are exclusively breastfed (24). However, in a small study involving only six infants, BH4 supplementation failed to reverse the IHPS clinical manifestations (8).…”
Section: Discussionmentioning
confidence: 96%
“…Breast milk, as opposed to infant formulas, has a high BH4 content (46), and IHPS rarely occurs in infants that are exclusively breastfed (24). However, in a small study involving only six infants, BH4 supplementation failed to reverse the IHPS clinical manifestations (8).…”
Section: Discussionmentioning
confidence: 96%
“…Transfusion has been shown to impair this postprandial increase in blood flow velocity in the superior MA (15). Circulating catecholamines (16,17), the sympathetic system, and endothelin (6) are considered to be primary constrictors of the mesenteric circulation. Therefore, we used NE and ET-1 as the constricting agents for isolated mesenteric arterial ring studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not the case and may be explained by observations from several studies that BH4 can cross the placenta (295), is also found in breast milk (306) and that maternal transfer of both BH4 and catecholamines can occur (273).…”
Section: Role Of Bh4 In Cardiovascular Developmentmentioning
confidence: 96%